2019
DOI: 10.1038/s41598-019-52911-1
|View full text |Cite
|
Sign up to set email alerts
|

Low mutation rate in the TTN gene in paediatric patients with dilated cardiomyopathy – a pilot study

Abstract: Idiopathic dilated cardiomyopathy (DCM) is a common cardiomyopathy with the prevalence of 1:250, and at least one-third of all the cases are inherited. Mutations in the TTN gene are considered as the most frequent cause of inherited DCM and cover 10–30% of the cases. The studies were mainly focused on the adult or mixed age group of patients with DCM. The mutation rate in the TTN gene, the characteristics of manifestations and their prognostic significance in childhood have not been studied. To determine TTN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In children, reports of TTNtv are primarily from smaller studies and vary from $2%-13% with authors reaching different conclusions about the importance of TTN testing in younger children. 22,[49][50][51][52][53] Pugh et al identified causative TTN variants in a cohort of children but not infants (age 0-2), and TTN variants are the largest cause of DCM in 2-18 year olds. 49 They reported 10% (95% CI, 5.5%-30.6%) P/LP variants in TTN, though their sample size was small (n ¼ 29).…”
Section: Discussionmentioning
confidence: 99%
“…In children, reports of TTNtv are primarily from smaller studies and vary from $2%-13% with authors reaching different conclusions about the importance of TTN testing in younger children. 22,[49][50][51][52][53] Pugh et al identified causative TTN variants in a cohort of children but not infants (age 0-2), and TTN variants are the largest cause of DCM in 2-18 year olds. 49 They reported 10% (95% CI, 5.5%-30.6%) P/LP variants in TTN, though their sample size was small (n ¼ 29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 23 Others have reported TTN variants associated with DCM in childhood. 19 , 20 One important note from our study is that P/LP TTN variants determined by cardiac genetic testing in infancy may still be associated with life‐threatening cardiac outcomes.…”
Section: Discussionmentioning
confidence: 88%